Video Art: Psychological Status of Orphans from the Unrest in the Three Southern Thai Province - I-na Phuyuthanon (IJCAS (International Journal of Creative and Arts Studies), 2015)
The greatest loss caused by the insurgency in Narathiwat province which is in the south of Thailand is the lives of the orphans whose parents or beloved ones have been deprived among conflicts and violence. Even though the affected people have received different aids, such cases are not as important as the situation faced by the orphans. After the losses, no one truly pays attention to the extent to which the southern crisis affects these unfortunate children. Even in time of peace, the children who will become adults in future have to face and suffers from severe social biases at home and elsewhere. They also have to face violence and the lack of safety in their lives. This is a result of the fire of vengeance between local people and the government’s suppression which is a game of those villains in power. The orphans will have to sustain their lives alone despite some aids from the government and private sectors. In order to create social awareness of the orphans’ daily lives in Narathiwat province, which affects their psychological status, education, and security of individual, social, and country’s levels, the awareness is raised through video art creation. Video art is a form of art which can reflects the way of lives of those who suffer from losses by presenting the stories of those who have lost, especially in terms of mental status after the loss. Video arts also present views and cultures of the locals with motion pictures, picture placement, and actions and contemporary artistic framework to convey the important message to the society so that people will understand the reality. Video arts are produced based on the researcher’s viewpoints and attitudes gained from the five senses – vision, hearing, smell, taste and touch. Video art is also a type of media that fully responds to human’s imaginations.